Volume 6: Materials and Fabrication, Parts a and B 2009
DOI: 10.1115/pvp2009-77269
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Evaluation of Dissimilar Weld Joint Using Reactor Vessel Outlet Nozzle Mock-Up Model: Report 2

Abstract: In recent years, the occurrence of primary water stress corrosion cracking (PWSCC) in Alloy 600 weld regions of PWR plants has increased. In order to evaluate the crack propagation of PWSCC, it is required to estimate stress distribution including residual stress and operational stress through the wall thickness of the Alloy 600 weld region. In a national project in Japan for the purpose of establishing residual stress evaluation method, a test model was produced using the same fabrication process in Japanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As is well known, the welding residual stress is affected by many factors and varied complicated, and it is very expensive and time-consuming to investigate the welding residual stress, and sometime is impossible [7] . Therefore, welding residual stress simulation using finite element method (FEM) analysis has become increasingly common in crack analysis combined with experiments [8,9] . It has been found that the distribution of welding residual stress depends on several main factors such as structural dimensions, material properties, restraint conditions, heat input, number of welding pass and welding sequence [10] .…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the welding residual stress is affected by many factors and varied complicated, and it is very expensive and time-consuming to investigate the welding residual stress, and sometime is impossible [7] . Therefore, welding residual stress simulation using finite element method (FEM) analysis has become increasingly common in crack analysis combined with experiments [8,9] . It has been found that the distribution of welding residual stress depends on several main factors such as structural dimensions, material properties, restraint conditions, heat input, number of welding pass and welding sequence [10] .…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to pipe butt welds which typically involve a single weld. Recent works reveal that the presence of the SMW can affect welding residual stresses in the DMW, depending on the safe‐end length 20–23 . In addition, the length of the safe‐end varies, depending on design and on manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, nozzle components consist of several materials, for instance low alloy steels, Ni‐based alloys and stainless steels. Due to these complexities, according to our knowledge, no systematic results have yet been presented, and existing works have been focused on specific nozzles 20–22,24–26 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations